QCD corrections to nonstandard WZ + jet production with leptonic decays at the LHC - Campanario Pallás, Francisco; Englert, Christoph; Spannowsky, Michael (Physical review. D, Particles, fields, gravitation, and cosmology, 2010)
We discuss the impact of anomalous WWγ and WWZ couplings on WZ+jet production at next-to-leading order QCD, including full leptonic decays of the electroweak gauge bosons. While the inclusive hadronic cross sections do not exhibit any particular sensitivity to anomalous couplings once the residual QCD scale uncertainties are taken into account, the transverse momentum distributions show substantial deviations from the standard model, provided that the anomalous vertices are probed at large enough momentum transfers.
Gesehen am 29.03.2023